Precision and agreement of higher order aberrations measured with ray tracing and Hartmann-Shack aberrometers - Zequan Xu; Yanjun Hua; Wei Qiu; Guoqiang Li; Qiang Wu (BMC Ophthalmology, 2018)
Abstract Background To assess the precision and agreement of measurements of higher order aberrations (HOAs) obtained with a ray tracing aberrometer (iTrace) and a Hartmann-Shack aberrometer (Topcon KR-1 W). Methods Prospective evaluation of the diagnostic test. Data from the right eyes of 92 normal subjects obtained using the two devices were included in this study. Two observers performed 3 consecutive scans to determine the intraobserver repeatability and interobserver reproducibility. About one week later, one observer performed an additional 3 consecutive scans to obtain the intersession reproducibility. The within-subject standard deviation (Sw), test-retest repeatability (TRT) and intraclass correlation coefficient (ICC) were used to assess the precision, while Bland-Altman plots were performed to assess the agreement. Results For intraobserver repeatability of the ocular, corneal and internal HOAs, Topcon KR-1 W showed a 2.77Sw of 0.079 μm or less and ICCs of 0.761 or more; and iTrace showed a 2.77Sw of 0.105 μm or less and ICCs of 0.805 or more. The ICCs of the internal HOAs of interobserver reproducibility were less than 0.75 except for spherical aberration (SA) (0.862), and interobserver reproducibility of the counterpart showed similar but lower results. For the ocular, corneal and internal HOA measurements, statistically significant differences existed between the Topcon KR-1 W and iTrace (all P < 0.05). No significant differences were observed in the ocular SA and internal coma. Conclusions The ray tracing and Hartmann-Shack method aberrometers provided excellent repeatability but less reliable reproducibility in the measurement of HOAs (except for SA). The two aberrometers should not be interchangeable in clinical application because of the significant differences in HOA measurements between them.